Major Domains of Internet of Things (IOTS) Based Applications and Associated Challenges - Patel, Dharmendra; Vyas, Pranav; Patel, Atul (International Journal of Computer Sciences and Engineering, 2019)
In recent years Internet of Things (IoTs) concept has expanded in massive impetus due to very good Internet infrastructure everywhere. IoT has the ability to creating a network of physical things that use embedded technologies in order to sense, converse, cooperate, and team up with other things. IoT sets up sophisticated connectivity among physical things in order to make automation in specific areas. Several applications have been developed in all domains, based on IoT concepts, to collaborate with other physical things in order to achieve atomization in that area. This paper will focus on major applications of Internet of Things (IoTs) on various application domains. Internet of Things (IoTs) process is very complex in order to team up with other physical objects and deals with many challenges. This paper will also discuss with challenges of IoTs in various application domains.